Distribution of fluorescent Pseudomonas spp. causing grain and sheath discoloration of rice in Latin America - Zeigler, Robert S.; Aricapa, María Girlena; Hoyos, E. (Scientific Societies, 1987)
Pathogenic fluorescent Pseudomonas spp. were isolated from discolored rice seed and flag-leaf sheath samples received from Argentina, Bolivia, Brazil, Burundi, Chile, China, Colombia, Costa Rica, Cuba, Dominican Republic, Ecuador, El Salvador, Guatemala, Jamaica, Nicaragua, Panama, Peru, Philippines, Surinam, and Uruguay. No such pathogens were recovered from samples received from Thailand. Pseudomonas syringae pv. syringae (= P. oryzicola) was found only in Chilean samples, whereas all the others yielded bacteria consistent with P. fuscovaginae. Antisera developed from P. fuscovaginae were not completely specific for this species, reacting as well with strains from Chile tentatively identified as P. syringae pv. syringae. However, the relationship between pathogenicity of strains and positive serological reaction was very high. The antisera were successfully used to increase the efficiency of pathogen isolation from diseased plant tissue. The presence of these pathogens and the dirty panicle disease of rice are correlated; however, not all cases of discolored grain should be ascribed to these pathogens.